Prinsip Keadilan Restoratif Dalam Penghentian Penuntutan Melalui Kompensasi dan Restitusi - Lukas Permadi Orlando Beremanda; Hafrida Hafrida; Elizabeth Siregar (Fakultas Hukum, Universitas Jambi, 2023)
This article aims to analyze the principle of restorative justice in ending prosecution through compensation and restitution. The involvement of victims and perpetrators of criminal acts determines the success or failure of the termination of prosecution based on restorative justice. The interests of both parties must be equal and balanced. This type of research is normative juridical research. The results of the study show that the provision of compensation and restitution is a manifestation regarding the state's obligation to assist individuals who are the victims of crimes. The failure to terminate the prosecution based on restorative justice is due to the failure to reach an agreement on compensation, where the victim often asks for compensation so large that the perpetrators of criminal acts are unable to pay it. When the state should protect the interests of the perpetrators of criminal acts, The government must protect the victims' interests by providing compensation and restitution. With the provision of compensation and restitution, it is hoped that it will increase the success of ending prosecution based on restorative justice. Abstrak Artikel ini bertujuan untuk menganalisis mengenai prinsip keadilan restoratif dalam penghentian penuntutan melalui kompensasi dan restitusi. Keterlibatan pihak korban dan pelaku tindak pidana sangat menentukan berhasil atau tidaknya penghentian penuntutan berdasarkan keadilan restoratif. Kepentingan kedua pihak perlu seimbang serta sama. Jenis penelitian merupakan penelitian yuridis normatif. Hasil penelitian menunjukkan bahwa pemberian kompensasi dan restitusi merupakan wujud tanggung jawab negara pada warga negara dimana jadi korban tindak pidana. Tidak tercapainya penghentian tuntutan didasarkan keadilan restoratif disebabkan tidak tercapainya kesepakatan ganti kerugian, dimana pihak korban selalu minta ganti kerugian sangat besar sehingga pelaku tindak pidana tidak sanggup untuk membayarnya. Harusnya saat negara melindungi kepentingan pelaku tindak pidana maka harusnya negara pun menjamin kepentingan pihak korban dari kompensasi dan restitusi. Dengan adanya pemberian kompensasi serta restitusi diharap bisa meningkatkan keberhasilan penghentian penuntutan berdasarkan keadilan restoratif.